The impact of ChatGPT on the critical thinking ability of UIN Sunan Kalijaga students - Akastangga, Muhammad Dedad Fajarsodiq; Harmonis, Sri; Al Hafidz, Rafi Alaudin (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2023)
This study aims to identify and analyze the impact of using ChatGPT, an artificial intelligence (AI) language, on students' critical thinking. The use of ChatGPT is becoming common at this time to get information and instant needs of students. However, the impact on critical thinking skills in students still needs to be studied. This research method uses quantitative methods. Giving questionnaires to a group of students who use ChatGPT is carried out online, data from this study is used to identify the impact of using ChatGPT on students' critical thinking levels. Using quantitative methods and online questionnaires, the study was able to collect relevant and detailed data on the impact of using ChatGPT. This makes it easier for researchers to identify data, as well as provide a deeper understanding of ChatGPT's influence on students' critical thinking. The results in the research we have done obtained 3.593 on the Likert scale. This shows that ChatGPT has a moderate effect on critical thinking skills. Dependence on the use of ChatGPT can reduce the level of critical thinking skills. Therefore, it is important to remember that although this study obtained positive results, the use of ChatGPT should be balanced with the development of independent critical thinking skills and critical evaluation of the information provided by the AI model.